2009
DOI: 10.1111/j.1439-0272.1992.tb02655.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryptorchidism: incidence and sperm quality in infertile men

Abstract: In a population of 8500 men attending the andrology outpatient clinic, 200 men (2.35%) were recorded as having some disturbances with the descent of the testes into the scrotum. Medical history of the patients revealed that 5 1 underwent unilateral orchidopexy; 40 bilateral orchidopexy; and 24 were treated with human chorionic gonadotropin in order to induce descent of their testes. In addition, 6 patients reported spontaneous descent of the testes, and 13 others were found to be unilaterally cryptorchid upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 19 publications
0
3
0
5
Order By: Relevance
“…Four studies were judged good quality, 27,45,49,52 1 fair quality, 32 and the remainder poor quality. [28][29][30][31][33][34][35][36][37][38][39][40][42][43][44][46][47][48]50,51,53 Eleven studies reported outcomes after either 1-stage FS orchiopexy, 2-stage FS orchiopexy, or primary orchiopexy. [36][37][38][39][40][42][43][44][45]47,48 Nine of these studies, all retrospective cohorts, provided success rates by surgical procedure, although the choice of surgical method is made clinically and not with the intent of comparative effectiveness.…”
Section: Effectiveness Of Surgical Proceduresmentioning
confidence: 99%
“…Four studies were judged good quality, 27,45,49,52 1 fair quality, 32 and the remainder poor quality. [28][29][30][31][33][34][35][36][37][38][39][40][42][43][44][46][47][48]50,51,53 Eleven studies reported outcomes after either 1-stage FS orchiopexy, 2-stage FS orchiopexy, or primary orchiopexy. [36][37][38][39][40][42][43][44][45]47,48 Nine of these studies, all retrospective cohorts, provided success rates by surgical procedure, although the choice of surgical method is made clinically and not with the intent of comparative effectiveness.…”
Section: Effectiveness Of Surgical Proceduresmentioning
confidence: 99%
“…Quels que soient le côté et le type de traitement, le volume du testicule anciennement cryptorchide est significativement plus petit que celui du testis controlatéral normalement descendu [83,[91][92][93][94]. Cette réduction du volume est un phénomène précoce, observé dès l'âge de 4-11 mois [95] ; elle ne semble pas être corrigée par l'orchidopexie, le déve-loppement testiculaire après la puberté étant diminué par rapport au controlatéral normalement descendu [96].…”
Section: Antécédent De Cryptorchidie Unilatéraleunclassified
“…En cas d'antécédent de cryptorchidie bilatérale, chacun des deux testicules a un volume significativement plus petit que ceux d'une population témoin sans antécédent de cryptorchidie [83,93]. Il ressort ainsi de l'ensemble de ces études de population que le volume moyen d'un testicule cryptorchide traité par orchidopexie dans l'enfance est réduit à l'âge adulte.…”
Section: Antécédent De Cryptorchidie Bilatéraleunclassified
See 2 more Smart Citations